THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND FAMILY ENVIRONMENT ON ENTREPRENEURSHIP INTERESTS OF ECONOMIC EDUCATION STUDENTS OF SEBELAS MARET UNIVERSITY - Rinda Oktia Wati; Sudarno Sudarno; Leny Noviani (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to determine (1) the influence of entrepreneurship education on the entrepreneurial interest of UNS Economics Education students, (2) the influence of the family environment on the entrepreneurial interest of UNS Economics Education students. This research is a quantitative descriptive research with a population of 330 Economics Education Study Program students. The sampling technique used in this research was proportionate random sampling which resulted in a sample of 77 respondents. Data collection is carried out through questionnaires which are distributed using a Google Form link or filled in directly. The data analysis used is multiple linear regression analysis with SPSS 26. The results shown from this research are: first, entrepreneurship education has a positive effect on the entrepreneurial interest of UNS Economics Education students as evidenced by the regression coefficient of 0.458, t value (4,696) > t table (1.991) and sig. (0.001) < 0.05. Second, the family environment has a positive effect on the entrepreneurial interest of UNS Economics Education students as evidenced by the regression coefficient of 0.390, t value (3,867) > t table (1.991) and sig. (0.001) < 0.05.